International Conference on Applications and Techniques in Cyber Security and Intelligence Applications and Techniques in Cyber Security and Intelligence - Abawajy, Jemal; Choo, Kim-Kwang Raymond; Islam, Rafiqul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Edizioni della Normale, 2018)
This book presents the outcomes of the 2017 International Conference on Applications and Techniques in Cyber Security and Intelligence, which focused on all aspects of techniques and applications in cyber and electronic security and intelligence research. The conference provides a forum for presenting and discussing innovative ideas, cutting-edge research findings, and novel techniques, methods and applications on all aspects of cyber and electronic security and intelligence.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence